2005
DOI: 10.1093/brain/awh416
|View full text |Cite
|
Sign up to set email alerts
|

A PET study exploring the laterality of brainstem activation in migraine using glyceryl trinitrate

Abstract: Migraine is a common disabling condition likely to be associated with dysfunction of brain pathways involved in pain and other sensory modalities. A cardinal, indeed signature, feature of the disorder that led to its name is that the pain may be lateralized. H(2)15O-labelled PET was used to study 24 migraineurs and eight healthy controls. The migraineurs were divided into three groups according to the site of their headache: right, left or bilateral. In each group, a migraine was induced using a glyceryl trini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
380
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(406 citation statements)
references
References 42 publications
20
380
1
5
Order By: Relevance
“…Further evidence for deficient inhibition comes from a study reporting hypofunctional structures in the midbrain in migraineurs (Moulton et al, 2008). Moreover, impaired iron homeostasis in the PAG (Welch et al, 2001;Kruit et al, 2009) and highly specific activation in the rostral pons (localization of the locus coreleus) during an acute migraine attack have been observed (Weiller et al, 1995;Afridi et al, 2005). In line with this latter finding, we also observed-for the first time using fMRI-that migraineurs showed a significant increase in activation of rostral parts of the pons during trigeminonociceptive stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence for deficient inhibition comes from a study reporting hypofunctional structures in the midbrain in migraineurs (Moulton et al, 2008). Moreover, impaired iron homeostasis in the PAG (Welch et al, 2001;Kruit et al, 2009) and highly specific activation in the rostral pons (localization of the locus coreleus) during an acute migraine attack have been observed (Weiller et al, 1995;Afridi et al, 2005). In line with this latter finding, we also observed-for the first time using fMRI-that migraineurs showed a significant increase in activation of rostral parts of the pons during trigeminonociceptive stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Migraineurs are characterized by an alteration of the interictal cortical excitability level, pointing to a deficit of filter mechanisms that is believed to protect individuals against sensory overload (Aurora et al, 2007;Coppola et al, 2007). During the headache attack, the function of brainstem nuclei involved in endogenous pain control and pain transmission is thought to be altered (Afridi et al, 2005;Lambert and Zagami, 2009). Consequently, a dysfunction of peripheral and central parts of the trigeminovascular system is of specific interest (Borsook et al, 2006;DaSilva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging with positron emission tomography (PET) shed light on the genesis of two of the most important headache syndromes, documenting activation in the midbrain and pons in migraine (Afridi et al, 2005) and in the hypothalamic gray in cluster headache (CH) (May et al, 1998;Sprenger et al, 2004). These areas are not simply involved as a response to first division nociceptive pain impulses but are inherent to each syndrome, probably in some permissive or dysfunctional role (Goadsby, 2002;May, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…8,11) Positron emission tomography studies have revealed that significant activation is seen in the brainstem, especially in the dorsal lateral pons, in patients with migraine without aura 13) and migraine triggered by 1,2-glyceryl trinitrate. 2,3) Therefore, involvement of the dorsal lateral pons is thought to initiate migraine or migraine-like headache. 1,8,10,11) Interestingly, one case involved a lesion located in almost the same region as in the present case.…”
Section: Discussionmentioning
confidence: 99%